Análisis del proceso administrativo en la Constructora Ulloa - Pérez Espinosa, Dayana Nicol (2022)
The objective of the work is to analyze how the administrative process is developed in Constructora Ulloa, based on the perceptions of the different internal stakeholders. The research approach was qualitative of descriptive type, using as theoretical methods, the historical-logical, to know the different stages of the administrative process in chronological succession, demonstrating its evolution and development, as well as its fundamental historical connections. Likewise, direct observation and the semi-structured interview were used as empirical methods, supported by instruments that allowed the collection of primary information. The interview was applied to the company's personnel, considering the different hierarchical levels and seniority within the company as selection criteria. The results obtained allowed to know how each of the stages of the administrative process is executed, allowing to establish areas of improvement according to the different findings, in relation to decision making, procedures, objectives, goals, plans and programs required for the continuous improvement of Constructora Ulloa.